Shear Bond Behaviour of Elemental Composite Beams with Different Configurations - Saavedra-Flores, E; Avudaiappan-, S (Elsevier Ltd, 2019)
In this study, an experimental program for testing steel concrete composite slabs subjected to symmetrical double line loads has been carried out to investigate the longitudinal shear bond behaviour. Different configurations of steel concrete composite slabs with and without embossments were studied. The flexural characteristics, ultimate strength and bond strength (end slip test) of composite slabs were determined. Partial connection (PC) approach was used to predict the longitudinal shear bond. The embossments in the profile decks slightly enhanced the longitudinal shear resistance and load carrying capacity (especially, at the end of the plastic stage), and also delayed debonding. Two failure modes, brittle and ductile phases, were observed during the tests. The experimental results demonstrated that the embossments do not have promising contributions to longitudinal shear strength and ductility of the composite slab elements, especially to elastic and plastic behaviour stages prior to the ultimate load carrying capacity. This study proposes a semi empirical formula (SEF) to evaluate the shear stress using simplification of the m-k method. The proposed SEF method was validated with data obtained from literature, showing an acceptable level of reliability and therefore, it could represent a good alternative for m-k and PC methods. © 2019 Elsevier Ltd